School's Out. - Burke, Lilah (American Prospect, 2024)
The article presents the discussion on challenges faced by small liberal arts colleges, like the College of Saint Rose. Topics include closed due to financial difficulties, forcing students to reconsider their academic and career plans; and program cuts, declining enrollment, and the broader trend of college closures and mergers.